Multiple scattering of Bessel beams propagating in advection fog and radiation fog - Chen, Run; Zhang, Yuanyuan; Xu, Qiang; Han, Yiping; Wu, Zhensen (Frontiers in Physics, 2024)
The Bessel beams scattering of the fog particles were calculated by using the plane beams angle spectrum expansion method, and the effects of the topological charge and the half-conic angle of the Bessel beam on the differential scattering cross-section were analyzed by numerical calculation. Based on the scattering results of a single fog particle by a Bessel beam, by Monte Carlo method, the propagation characteristics of the Bessel beam in fogs with different visibility are simulated, and the effects of the wavelength, topological charge and semi-conic angle of the Bessel beam on transmissivity and reflectivity are analyzed. The studies show the self-healing ability of the Bessel beams, and the propagation distance of the Bessel beam is longer than that of the plane beams in fogs.